HUBUNGAN FAKTOR INDIVIDU DENGAN KEJADIAN KECELAKAAN KERJA PADA SUPIR BUS - Helmy Astiza Rut Hanani; Nugrahadi Dwi Pasca Budiono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Buses are an essential mode of transportation that support human social needs; however, working as a bus driver carries high risks of occupational and traffic accidents. Individual factors such as fatigue, concentration levels, and knowledge of occupational safety significantly influence the risk of accidents, with fatigue being the primary cause as it reduces concentration and slows reaction times. This study aims to identify the relationship between individual factors and occupational accidents among bus drivers, as well as to offer practical solutions to improve workplace safety. The study adopts an explanatory research method with a quantitative approach to examine the causal relationship between independent and dependent variables, with data collected through questionnaires and analyzed using SPSS. The analysis includes statistical tests such as multiple linear regression, hypothesis testing, and determination coefficients to evaluate the effect of individual factors such as fatigue, concentration, and physical health on occupational accidents among bus drivers. The results of this study indicate that fatigue and concentration have a significant relationship with occupational accidents among bus drivers, with 67.9% of cases explained by these factors. High levels of fatigue and low concentration increase the risk of accidents due to reduced responsiveness to emergency situations. Driver behavior also has a significant relationship with accidents, although their behavior is generally categorized as good. Other factors such as fatigue and physical condition also contribute simultaneously to accidents. Workplace safety can be improved through work schedule adjustments, training, supervision, and providing incentives to encourage safe driving behavior.